SURVIVE TO THRIVE : How Finnish universities make use of futures knowledge in the 2021-2030 strategy - Witoon, Siyada (My University, 2021)
Futures knowledge refers to the understandings of a coming event generated by the change observation and interpretation of multidisciplinary viewpoints. It is a learning capability and cognition of change that influence future actions. In the era of VUCA (volatility, uncertainty, complexity, and ambiguity), the futures knowledge can benefit organizations to prepare and strategize their behaviors to cope with uncertain future. As the higher education institutions are knowledge producers, communicators, and multipliers, the study of futures knowledge at the university level become an interesting subject. This research selects four Finnish universities as case studies to investigate three important questions: 1) to what extent futures knowledge is used in the development of 2021 to 2030 strategies at the university level, 2) how futures knowledge of Finnish universities can impact Finnish higher education at the end of 2020s, and 3) how the university futures knowledge is related to the higher education strategy of Finnish government in 2021 to 2030. The research finding shows that the futures knowledge of the Finnish universities refers to the speculation and interpretation of general and educational trends. The institutions gather futures knowledge from different sources including the university proximate and extended communities, academic and non-academic research, and the government recommendation papers. While the university communities are the most exhaustive source of futures knowledge, the government roadmap is the most influential source that determines the future action-taking of the Finnish universities. This means the change and impacts that the Finnish academic institutions will bring by 2030 correspond with the Finnish government that aim to internationalize higher education, in-crease the impacts of research, create larger networks and partnership in business sec-tors, and promote digitalization and well-being of the academic community. To survive, the Finnish universities utilizes the government roadmaps as a frame to shape their futures knowledge and develop a strategy to answer the expectation of the government to access to their financial support. To thrive, the Finnish universities may need to push forward their agenda that reflect the needs and desire of their community, the greatest contributor of the futures knowledge at the university level. This can result in the community empowerment and the better quality of futures knowledge for strategic thinking.
Keywords: Futures knowledge, university strategy, higher education public policy.